(untitled) (Journal of Student Affairs in Africa, 2021)
First-year seminars and university induction programmes are embedded with academic and social skills required by students to transition into their first year of study. The first-year seminar at the Universityof the Free State is a credit-bearing module called UFS101, and is a prerequisite for degree completion. Students are assessed through summative assessment opportunities throughout the year. In 2020, the UFS101 module embarked on new territory by condensing the contact time for the first semester into a week-long summer school. Furthermore, the summer school was presented a week prior to the start of university, with repeat sessions during the first week of class, and during the March holiday. However, due to national lockdown regulations as a result of Covid-19, a part of the cohort had to self-study the content via an interactive online study guide. This created four distinct groups of students: those who attended face-to-face classes, some face-to-face classes and some self-study, self-study only, and students who could not access the content. In order to measure their transition into university, a questionnaire was distributed to the students, and the results were stratified according to one of the aforementioned categories. Unique similarities and differences were observed in the findings. The results depict that effective content design is at the heartbeat of student transition, but that other factors such as face-to-face interaction with students, and access to resources assist with the transition into university. This study highlighted the need to explore the challenges students experience within their first six months at university, and substantiates that this type of exploration should be routinely conducted to assist with the understanding and implementation of first-year student support.